Computed tomography-derived characterisation of pericoronary,epicardial and paracardial adipose tissue and its association with myocardial ischemia as assessed by computed and invasive fractional flow - Göller, Markus; Duncker, Hendrik; Moshage, Maximilian; Dey, D.; Bittner, Daniel; Ammon, Fabian; Achenbach, Stephan; Marwan, Mohamed (EUROPEAN HEART JOURNAL, 2021)
CRIS-Team WoS Importer:2021-12-10

Computed Tomography-derived Characterization of Pericoronary, Epicardial, and Paracardial Adipose Tissue and Its Association with Myocardial Ischemia as Assessed by Computed Fractional Flow Reserve - Duncker, Hendrik; Achenbach, Stephan; Moshage, Maximilian; Dey, Damini; Bittner, Daniel O.; Ammon, Fabian; Marwan, Mohamed; Oeller, Markus (Journal of Thoracic Imaging, 2023)
Background: Increased pericoronary adipose tissue (PCAT) attenuation derived from coronary computed tomography (CT) angiography (CTA) relates to coronary inflammation and cardiac mortality. We aimed to investigate the association between CT-derived characterization of different cardiac fat compartments and myocardial ischemia as assessed by computed fractional flow reserve (FFRCT). Methods: In all, 133 patients (median 64 y, 74% male) with coronary artery disease (CAD) underwent CTA including FFRCT measurement followed by invasive FFR assessment (FFRINVASIVE). CT attenuation and volume of PCAT were quantified around the proximal right coronary artery (RCA), left anterior descending artery (LAD), and left circumflex artery (LCX). Epicardial adipose tissue (EAT) and paracardial adipose tissue (PAT; all intrathoracic adipose tissue outside the pericardium) were quantified in noncontrast cardiac CT datasets. Results: Median FFRCT was 0.86 [0.79, 0.91] and median FFRINVASIVE was 0.87 [0.81, 0.93]. Subjects with the presence of myocardial ischemia (n=26) defined by an FFRCT-threshold of ≤0.75 showed significantly higher RCA PCAT attenuation than individuals without myocardial ischemia (n=107) (-75.1±10.8 vs. -81.1±10.6 HU, P=0.011). In multivariable analysis adjusted for age, body mass index, sex and risk factors, increased RCA PCAT attenuation remained a significant predictor of myocardial ischemia. Between individuals with myocardial ischemia compared with individuals without myocardial ischemia, there was no significant difference in the volume and CT attenuation of EAT and PAT or in the PCAT volume of RCA, LAD, and LCX. Conclusions: Increased RCA PCAT attenuation is associated with the presence of myocardial ischemia as assessed by FFR, while PCAT volume, EAT, and PAT are not.
CRIS-Team Scopus Importer:2023-01-06
Keywords: computed tomography attenuation; coronary computed tomography angiography; epicardial adipose tissue; fractional flow reserve; myocardial ischemia; paracardial adipose tissue; pericoronary adipose tissue

Imaging of the Pericoronary Adipose Tissue (PCAT) Using Cardiac Computed Tomography: Modern Clinical Implications - Göller, Markus; Achenbach, Stephan; Duncker, Hendrik; Dey, Damini; Marwan, Mohamed (Journal of Thoracic Imaging, 2021)
Modern coronary computed tomography angiography (CTA) is the gold standard to visualize the epicardial adipose tissue (EAT) and pericoronary adipose tissue (PCAT). The EAT is a metabolic active fat depot enclosed by the visceral pericardium and surrounds the coronary arteries. In disease states with increased EAT volume and dysfunctional adipocytes, EAT secretes an increased amount of adipocytokines and the resulting imbalance of proinflammatory and anti-inflammatory mediators potentially causes atherogenic effects on the coronary vessel wall in a paracrine way ("outside-to-inside" signaling). These EAT-induced atherogenic effects are reported to increase the risk for the development of coronary artery disease, myocardial ischemia, high-risk plaque features, and future major adverse cardiac events. Coronary inflammation plays a key role in the development and progression of coronary artery disease; however, its noninvasive detection remains challenging. In future, this clinical dilemma might be changed by the CTA-derived analysis of the PCAT. On the basis of the concept of an "inside-to-outside" signaling between the inflamed coronary vessel wall and the surrounding PCAT recent evidence demonstrates that PCAT computed tomography attenuation especially around the right coronary artery derived from routine CTA is a promising imaging biomarker and "sensor" to noninvasively detect coronary inflammation. This review summarizes the biological and technical principles of CTA-derived PCAT analysis and highlights its clinical implications to improve modern cardiovascular prevention strategies.
CRIS-Team Scopus Importer:2021-05-21
Keywords: atherosclerosis; computed tomography attenuation; computed tomography imaging; inflammation; pericoronary adipose tissue